A microwave-assisted highly practical chemoselective esterification and amidation of carboxylic acids. Issue 96 (30th September 2016) - Pathak, Gunindra; Das, Diparjun; Rokhum, Samuel Lalthazuala
Abstract : The ubiquitousness of esters and amide functionalities makes their coupling reaction one of the most sought-after organic transformations. Abstract : The ubiquitousness of esters and amide functionalities makes their coupling reaction one of the most sought-after organic transformations. Herein, we have described an efficient microwave-assisted synthesis of esters and amides. Soluble triphenylphosphine, in conjugation with molecular iodine, gave the desired products without the requirement for a base/catalyst. In addition, a solid-phase synthetic route is incorporated for the said conversion, which has added advantages over solution-phase pathways, such as low moisture sensitivity, easy handling, isolation of the product by simple filtration, and reusability. In short, our method is simple, mild, green, and highly chemoselective in nature.